Using Scattergories Game in Teaching Vocabulary to Elementary School Students - Norma Yuliansyah; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2018)
This article aims to describe the use of Scattergories game in teaching vocabulary to elementary school students. Vocabulary is a basic component in mastering the four language skills; listening, speaking, reading, and writing. Therefore, vocabulary must be taught to children from elementary education. Elementary school students or called